Quantifying spatial and temporal trends in the Bonney Upwelling over the past 30 years - Alex Shute; Tim Ward; Mary Young; Mark Doubell; Kay Critchell; Daniel Ierodiaconou (Continental Shelf Research, 2026)

Field-based AFDD for refrigerant undercharge in residential HVAC systems: enhancing reliability through false alarm mitigation - Young Jae Choi; Yeobeom Yoon; Piljae Im; Sungkyun Jung; Brian Kolar; Tim Dyer; Youngsik Choi (Energy and Buildings, 2026)

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Influence of Pt-metal alloy catalysts with various ionomers on oxygen reduction reaction in fuel cell application - Xiang Lyu; Tim Van Cleve; Haoran Yu; Erica Young; Leiming Hu; Jun Yang; K.C. Neyerlin; Alexey Serov (Journal of Environmental Chemical Engineering, 2026)

Global Fire Emissions Linked to Madden-Julian Oscillation - Young-Min Yang; Doo Young Lee; Jae-Heung Park; June-Yi Lee; Kyung-Sook Yun; Soon-Il An; Tim Li; Bin Wang (Advances in Atmospheric Sciences, 2025)
Understanding the relationship between fire activity and climate variability is a major concern for the scientific community and is essential for reducing economic losses and life-threatening fire hazards. However, the drivers of fire activity and the influence of climate variability remain uncertain. Here, we show that the Madden-Julian Oscillation (MJO)—a dominant tropical subseasonal variability—influences fire activity by modulating local fire-supporting weather through atmospheric teleconnections. Our results show that midlatitude fire emissions exhibit significant subseasonal variability, with MJO-related weather influencing the fire intensity and contributing to large fire events. MJO-related fire events account for about 10%–20% of total midlatitude fire events, suggesting that if MJO teleconnections strengthen in the future, fire emissions and associated economic losses could worsen.

Spatiotemporal changes of atmospheric depositions over 43 years in south-central Ontario - Huaxia Yao; Joelle Young; April James; David Lembcke; Christopher McConnell; Tim Field; Lance Aspden; Sara Rawski; Chris Jones; Michelle Palmer; Claire Holeton; James A. Rusak; et al. (Atmospheric Environment, 2025)

Sand tiger shark Carcharias taurus mating season in the northwest Atlantic Ocean inferred from wound healing dynamics - Jennifer T. Wyffels; Joshua Riter; Carol S. Price; Kate Poelzl; Brenda Young; Tim Handsel; Laura E. Edsberg (Environmental Biology of Fishes, 2025)
All sharks and rays reproduce using internal fertilization. This necessitates males and females to be coupled tightly during copulation, and as a result, bite wounds associated with mating occur. The appearance of these bite wounds can be used to gauge the timeframe of mating activity without direct observation of copulation. A wound staging system was developed for the sand tiger shark Carcharias taurus through longitudinal observations of an aquarium-housed female that sustained a full-thickness mating wound, an injury that extends through the epidermis, dermis, and hypodermis, exposing underlying muscle. Four wound stages were established: (1) full-thickness, (2) healing, (3) closure, and (4) scar revision. The female’s stage 1 (full thickness) wound transitioned to stage 2 (healing) 2 weeks post-injury. Stage 3 (wound closure) was observed 3–6 weeks post-injury and stage 4 (scar revision) followed and persisted for the duration of the study, 35 weeks post-injury. The staging system was used to characterize the incidence, severity, and etiology of wounds for in situ sharks aggregating at North Carolina shipwreck sites from digital images contributed to the Spot A Shark USA database. There was a significant association between wound stage and its location or zone on the body as well as season of the year for males and females. Mating wounds on females corroborate a late spring and early summer mating season. The presence of stages 1 and 2 mating wounds on sand tiger sharks in North Carolina suggests the area is used for mating while females with stages 3 and 4 mating wounds provide evidence that the area also serves as gestation habitat for this species. This research highlights minimally invasive methodology that leverages citizen science divers to further characterize the reproductive life history of sand tiger sharks.

Don't follow trends, start trends: PSMA implementation and port state performance from 2017 to 2023 - Gilles Hosch; Nathan A. Miller; Joseph Fader; Elaine Young; Yann Yvergniaux; Rachel Hanbury; Tim Huntington (Ocean & Coastal Management, 2025)

Estimating sediment delivery ratio using the RUSLE-IC-SDR approach at a complex landscape: A case study at the Lower Snowy River area, Australia - Xihua Yang; John Young; Haijing Shi; Qinggaozi Zhu; Ian Pulsford; Greg Chapman; Leah Moore; Angela G Gormley; Richard Thackway; Tim Shepherd (Journal of Hydrology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mitigation of Vibrio-Induced Metabolic Perturbations in Argopecten purpuratus Scallop Larvae via Probiotic Pretreatment - Katherine Muñoz-Cerro; Leonie Venter; Tim Young; Andrea C. Alfaro; Katherina Brokordt; Paulina Schmitt (Journal of Marine Science and Engineering, 2024)
Background: The decrease in the production of Argopecten purpuratus scallops in Chile is linked to extensive larval deaths in hatcheries caused by bacterial pathogens, particularly Vibrio genus, threatening sustainability. Traditional antibiotic practices raise concerns, urging research on eco-friendly strategies like bacterial probiotics. This study explores the metabolic responses of scallop larvae to Vibrio bivalvicida and evaluates the impact of the Psychrobacter sp. R10_7 probiotic on larval metabolism pre- and post-infection. Materials and Methods: Analysis detected 183 metabolite features, revealing significant changes in larval metabolites during Vibrio infection. Larvae pretreated with probiotics showed a metabolic profile comparable to non-infected larvae, indicating low impact on larval metabolome, likely due to probiotics antagonistic effect on pathogens. Results: Arachidonic acid, eicosatrienoic acid, docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and docosapentaenoic acid (DPA) were significantly higher in non-pretreated/infected larvae compared to both pretreated/infected and non-pretreated/non-infected larvae, potentially supporting the activation of immune response in non-pretreated larvae to Vibrio infection. Identification of 76 metabolites provided insights into scallop larvae metabolome, highlighting the enriched metabolic pathways associated with energy provision and immune response. Conclusions: Probiotic pretreatment may mitigate metabolic disruptions in scallop larvae caused by Vibrio infection, suggesting a promising strategy for sustainable scallop production.

Microbially-mediated reductive dissolution of Fe-bearing minerals during freeze-thaw cycles - Jinwook Kim; Young Kyu Park; Tae-hee Koo; Jaewoo Jung; Insung Kang; Kitae Kim; Hanbeom Park; Kyu-Cheul Yoo; Brad E. Rosenheim; Tim M. Conway (Geochimica et Cosmochimica Acta, 2024)

Interactive effects of elevated temperature and Photobacterium swingsii infection on the survival and immune response of marine mussels (Perna canaliculus): A summer mortality scenario - Awanis Azizan; Leonie Venter; Jingjing Zhang; Tim Young; Jessica A. Ericson; Natalí J. Delorme; Norman L.C. Ragg; Andrea C. Alfaro (Marine Environmental Research, 2024)

Quantification of Photobacterium swingsii and characterisation of disease progression in the New Zealand Greenshell™ mussel, Perna canaliculus - Awanis Azizan; Andrea C. Alfaro; Leonie Venter; Diana Jaramillo; Mark Bestbier; Peter Bennett; Jonathan Foxwell; Tim Young (Journal of Invertebrate Pathology, 2024)

Microplastic pollution on historic facades: Hidden ‘sink' or urban threat? - Katrin Wilhelm; Sam Woor; Michelle Jackson; Dania Albini; Neil Young; Phani Karamched; Miriam C. Policarpo Wright; Josep Grau-Bove; Scott Allan Orr; Jack Longman; Tim de Kock (Environmental Pollution, 2024)

Evaluation of cataract formation in fish exposed to environmental radiation at Chernobyl and Fukushima - Adélaïde Lerebours; Justyn Regini; Roy A. Quinlan; Toshihiro Wada; Barbara Pierscionek; Martin Devonshire; Alexia A. Kalligeraki; Alice Uwineza; Laura Young; John M. Girkin; Phil Warwick; Kurt Smith; et al. (Science of The Total Environment, 2023)

Metabolite profiling identifies chemical markers associated with the cytotoxic properties of roasted fermented avocado seeds - Zhiyu Zhao; Nazimah Hamid; Noemi Gutierrez-Maddox; Rothman Kam; Kevin Kantono; Kelvin Wang; Tim Young; Thao T. Le; Jun Lu (Food Research International, 2023)

IUU safe havens or PSMA ports: A global assessment of port State performance and risk - Gilles Hosch; Nathan A. Miller; Yann Yvergniaux; Elaine Young; Tim Huntington (Marine Policy, 2023)

An evaluation of the growth and immunity of New Zealand black-footed abalone (Haliotis iris) treated with encapsulated feed and probiotics - Seyedehsara Masoomi Dezfooli; Thao V. Nguyen; Tim Young; Noemi Gutierrez-Maddox; Andrea C. Alfaro; Ali Seyfoddin (Animal Feed Science and Technology, 2023)

An integrated proteomics and metabolomics investigation of feed efficiency in seawater reared Chinook salmon (Oncorhynchus tshawytscha) - Noah Esmaeili; Chris G. Carter; Richard Wilson; Seumas P. Walker; Matthew R. Miller; Andrew R. Bridle; Tim Young; Andrea C. Alfaro; Olivier Laroche; Jane E. Symonds (Aquaculture, 2023)

Pressing questions for science, policy, and governance in the high seas - Rebecca M. Jarvis; Tim Young (Environmental Science & Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mapping the Green-Lipped Mussel (Perna canaliculus) Microbiome: A Multi-Tissue Analysis of Bacterial and Fungal Diversity - Siming Li; Tim Young; Stephen Archer; Kevin Lee; Shaneel Sharma; Andrea C. Alfaro (Current Microbiology, 2022)
Poor health and mortality events of the commercially important and endemic New Zealand green-lipped mussel ( Perna canaliculus ) pose a threat to its industry. Despite the known importance of microbiomes to animal health and environmental resilience, the host-associated microbiome is unexplored in this species. We conducted the first baseline characterization of bacteria and fungi within key host tissues (gills, haemolymph, digestive gland, and stomach) using high-throughput amplicon sequencing of 16S rRNA gene and ITS1 region for bacteria and fungi, respectively. Tissue types displayed distinctive bacterial profiles, consistent among individuals, that were dominated by phyla which reflect (1) a fluid exchange between the circulatory system (gills and haemolymph) and surrounding aqueous environment and (2) a highly diverse digestive system (digestive gland and stomach) microbiota. Gammaproteobacteria and Campylobacterota were mostly identified in the gill tissue and haemolymph, and were also found in high abundance in seawater. Digestive gland and stomach tissues were dominated by common gut bacterial phyla, such as Firmicutes , Cyanobacteria , Proteobacteria , and Bacteroidota , which reflects the selectivity of the digestive system and food-based influences. Other major notable taxa included the family Spirochaetaceae , and genera Endozoicomonas , Psychrilyobacter , Moritella and Poseidonibacter , which were highly variable among tissue types and samples. More than 50% of fungal amplicon sequence variants (ASVs) were unclassified beyond the phylum level, which reflects the lack of studies with marine fungi. However, the majority of those identified were assigned to the phylum Ascomycota . The findings from this work provide the first insight into healthy tissue microbiomes of P. canaliculus and is of central importance to understanding the effect of environmental changes on farmed mussels at the microbial level.

Metabolomics in salmonid aquaculture research: Applications and future perspectives - Ronald Lulijwa; Andrea C. Alfaro; Tim Young (Reviews in Aquaculture, 2022)
Salmonids are the third major farmed finfish species after carps and tilapines, and thus contribute to global food fish production. However, as the aquaculture industry continues to grow, several challenges have emerged. Left unchecked, current problems will hinder aquaculture development. Metabolomics is one of the powerful biotechnological tools that will contribute to solving some of the pressing problems. This review aims to summarise findings and identify gaps from studies that used metabolomics in farmed salmon research. We extracted methodological information for comparison, highlighted analytical platform usages and identified most studied salmonids and sample types. We reviewed key articles to highlight the latest research themes. From the identified research gaps, future perspectives regarding potential use of metabolomics to solve issues in ecotoxicology, thermotolerance, nutrition, post‐harvest quality, health and disease, and husbandry practices are provided. The survey also highlighted improvements in execution of metabolomics protocols in aquaculture.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Haematological and metabolic profiles associated with age and sex in giant kokopu ( Galaxias argenteus ) ( Gmelin 1789) broodstock - Ronald Lulijwa; Andrea C. Alfaro; Leonie Venter; Tim Young; Paul Decker; Fabrice Merien; Jill Meyer (Journal of Fish Biology, 2021)
This study characterized selected peripheral blood (PB) haematological parameters, liver, serum and muscle metabolic features in 3‐ and 5‐year‐old male and female giant kokopu ( Galaxias argenteus ) broodstock reared indoor at 16°C. Sex and age did not affect PB total cell count and haematocrit values. Nonetheless, higher erythrocytes in 5‐year‐old fish, elevated thrombocyte and lymphocyte counts in 3‐year‐old fish indicate age‐specific cellular regulation. Higher thrombocyte counts in female fish suggest sex‐specific regulation. At a metabolic level, liver abundance for long chain saturated fatty acids (FAs) was higher in males, whereas females had elevated levels of polyunsaturated FAs. Essential and non‐essential amino acids (AAs) in liver and serum were also elevated in females compared to males. These findings suggest differential allocation of FAs and AAs to reflect requirements for gonadal, development and provisioning. Similarly, age significantly resulted in higher liver and serum abundances of some non‐essential AAs in 3‐year‐olds compared to 5‐year‐old fish, suggesting higher metabolism in younger fish. Overall, results enhance our understanding of sex‐ and age‐based differences in fish haematology, muscle, liver, and serum metabolite profiles in healthy G. argenteus . Future studies should carefully consider potential age‐ and sex‐specific differences in metabolic responses.

Effect of anticoagulants on farmed giant kokopu, Galaxias argenteus (Gmelin 1789) haematological parameters and erythrocyte fragility - Ronald Lulijwa; Andrea C. Alfaro; Tim Young; Leonie Venter; Paul Decker; Fabrice Merien; Jill Meyer (Journal of Fish Biology, 2021)
We sought to determine a compatible anticoagulant for routine haematological and physiological assessments with giant kokopu ( Galaxias argenteus ), an endemic New Zealand fish. We observed that blood treated with lithium heparin (LH) rapidly coagulated and haemolysed, making it unsuitable for G. argenteus . Dipotassium ethylenediaminetetraacetic acid (K 2 EDTA) and trisodium citrate (citrate) effectively prevented blood coagulation. K 2 EDTA‐treated erythrocytes exhibited the least mean haemolysis and mean corpuscular fragility. Further studies into prolonged storage effects of citrate and K 2 EDTA are recommended to find a compatible anticoagulant for use with G. argenteus blood.

Mid‐latitude leading double‐dip La Niña - Jae‐Heung Park; Soon‐Il An; Jong‐Seong Kug; Young‐Min Yang; Tim Li; Hyun‐Su Jo (International Journal of Climatology, 2021)
Understanding the evolution asymmetry between El Niño and La Niña events is challenging. Unlike El Niño, most La Niña events are characterised by a double‐dip cooling (a.k.a. multi‐year La Niña). Herein, we examined how single‐ and multi‐year La Niña events differ by analysing observational and climate‐model data sets. Single‐year La Niña events tend to develop narrowly within the tropics from a central Pacific‐type El Niño (Niño‐4 > Niño‐3), whereas multi‐year La Niña events tend to originate from an eastern Pacific‐type El Niño (Niño‐3 > Niño‐4) and are well‐connected to mid‐latitudes through the Pacific meridional mode , which leads to a meridionally wider response of the off‐equatorial low‐level atmospheric anti‐cyclonic circulation. As the anti‐cyclonic circulation controls the amount of equatorial upper‐ocean heat recharge through Sverdrup transport, for single‐year La Niña, efficient ocean recharging due to a narrower anti‐cyclonic circulation causes a fast transition to an El Niño or a fast termination of a La Niña. In contrast, for multi‐year La Niña, a weaker recharging causes surface cooling to persist, leading to another La Niña in the following year.

Polyinosinic:polycytidylic acid in vivo enhances Chinook salmon (Oncorhynchus tshawytscha) immunity and alters the fish metabolome - Ronald Lulijwa; Andrea C. Alfaro; Fabrice Merien; Mark Burdass; Jill Meyer; Leonie Venter; Tim Young (Aquaculture International, 2020)

Predators, Disease, and Environmental Change in the Nearshore Ecosystem: Mortality in Southern Sea Otters (Enhydra lutris nereis) From 1998–2012 - Melissa A. Miller; Megan E. Moriarty; Laird Henkel; Martin Tim Tinker; Tristan L. Burgess; Francesca I. Batac; Erin Dodd; Colleen Young; Michael D. Harris; David A. Jessup; Jack Ames; Patricia A. Conrad; et al. (Frontiers in Marine Science, 2020)
We compiled findings from 15 years (1998–2012) of southern sea otter ( Enhydra lutris nereis ) necropsies, incorporating data from 560 animals. Sensitive diagnostic tests were used to detect biotoxins, bacteria, parasites and fungi. Methods to classify primary and contributing causes of death (COD) and sequelae utilized an updated understanding of health risks affecting this population. Several interesting patterns emerged, including identification of coastal regions of high mortality risk for sea otter mortality due to shark bite, cardiomyopathy, toxoplasmosis, sarcocystosis, acanthocephalan peritonitis and coccidioidomycosis. We identified demographic attributes that enhanced the risk of disease in relation to age, sex, and reproductive stage. Death due to white shark ( Carcharodon carcharias ) bite increased dramatically during the study period and was the most common primary COD. However, when primary and contributing COD were combined, the most prevalent COD was infectious disease (affecting 63% of otters), especially fatal infections by acanthocephalans ( Profilicollis spp.) and protozoa (e.g., Sarcocystis neurona and Toxoplasma gondii ). Fatal bacterial infections were also extremely common as a primary process or a sequela, affecting 68% of examined otters. Substantial advances were made in identifying sea otters that died following exposure to the pervasive marine neurotoxin domoic acid (DA), and DA intoxication was conservatively estimated as a primary or contributing COD for 20% of otters. Cardiomyopathy was also highly prevalent as a primary or contributing COD (41%) and exhibited significant associations with DA intoxication and protozoal infection. For adult and aged adult females in late pup care through post-weaning at the time of death, 83% had end lactation syndrome (ELS) as a primary or contributing COD. This comprehensive longitudinal dataset is unique in its depth and scope. The large sample size and extensive time period provided an opportunity to investigate mortality patterns in a changing environment and identify spatial and temporal disease “hot spots” and emerging threats. Our findings will help improve estimates of population-level impacts of specific threats and optimize conservation and environmental mitigation efforts for this threatened species.

Metabolic and immune responses of Chinook salmon ( Oncorhynchus tshawytscha ) smolts to a short‐term poly (I:C) challenge - Ronald Lulijwa; Andrea C. Alfaro; Fabrice Merien; Mark Burdass; Jill Meyer; Leonie Venter; Tim Young (Journal of Fish Biology, 2020)
Polyinosinic:polycytidylic acid [poly (I:C)] was administered in vivo to Chinook salmon ( Oncorhynchus tshawytscha ) post‐smolts to determine the immune responses on haematological and cellular functional parameters, including spleen (SP), head kidney (HK) and red blood cell (RBC) cytokine expression, as well as serum metabolomics. Poly (I:C) in vivo (24 h exposure) did not affect fish haematological parameters, leucocyte phagocytic activity and phagocytic index, reactive oxygen species and nitric oxide production. Gas chromatography–mass spectrometry–based metabolomics revealed that poly (I:C) significantly altered the serum biochemistry profile of 25 metabolites. Metabolites involved in the branched‐chain amino acid/glutathione and transsulphuration pathways and phospholipid metabolism accumulated in poly (I:C)–treated fish, whereas those involved in the glycolytic and energy metabolism pathways were downregulated. At cytokine transcript level, poly (I:C) induced a significant upregulation of antiviral ifnγ in HK and Mx1 protein in HK, SP and RBCs. This study provides evidence for poly (I:C)–induced, immune‐related biomarkers at metabolic and molecular levels in farmed O. tshawytscha in vivo . These findings provide insights into short‐term effects of poly (I:C) at haematological, innate and adaptive immunity and metabolic levels, setting the stage for future studies.

Impact of acute handling stress, anaesthesia, and euthanasia on fish plasma biochemistry: implications for veterinary screening and metabolomic sampling - Tim Young; Seumas P. Walker; Andrea C. Alfaro; Lauren M. Fletcher; J. Sam Murray; Ronald Lulijwa; Jane Symonds (Fish Physiology and Biochemistry, 2019)

Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean - Alexander V. Babanin; W. Erick Rogers; Ricardo de Camargo; Martin Doble; Tom Durrant; Kirill Filchuk; Kevin Ewans; Mark Hemer; Tim Janssen; Boris Kelly-Gerreyn; Keith Machutchon; Peter McComb; et al. (Frontiers in Marine Science, 2019)

SACS variants are a relevant cause of autosomal recessive hereditary motor and sensory neuropathy - Katharina Vill; Wolfgang Müller-Felber; Dieter Gläser; Marius Kuhn; Veronika Teusch; Herbert Schreiber; Joachim Weis; Jörg Klepper; Anja Schirmacher; Astrid Blaschek; Manuela Wiessner; Tim M. Strom; et al. (Human Genetics, 2018)

Seasonal bulk xylem pressure in temperate broadleaf eudicot trees: a case study for sugar long-distance transport and signaling - Ross Young; Root Gorelick; Tim Xing (Tree Genetics & Genomes, 2018)

Metabolomics Study of Immune Responses of New Zealand Greenshell™ Mussels (Perna canaliculus) Infected with Pathogenic Vibrio sp. - Thao V. Nguyen; Andrea C. Alfaro; Tim Young; Sridevi Ravi; Fabrice Merien (Marine Biotechnology, 2018)

Metabolomic strategies for aquaculture research: a primer - Tim Young; Andrea C. Alfaro (Reviews in Aquaculture, 2018)
Metabolomics is a fast‐evolving field that provides qualitative and quantitative analyses of metabolites within cells, tissues or biofluids. Recent applications of metabolomics approaches in aquaculture research have highlighted the huge potential for solving problems within all aspects of the production line, from hatchery production to post‐harvest quality control. To assist with the growing application of metabolomics in aquaculture research, this contribution provides a review of techniques and steps necessary to conduct metabolomics research, from experimental design to data interpretation. Specifically, we target scientists who are new to the field of metabolomics, and we offer simple, but comprehensive steps and strategies to conduct this type of research. We conclude this primer with some advice on how to access relevant expertise and facilities for metabolomics‐based aquaculture research.

Showcasing metabolomic applications in aquaculture: a review - Andrea C. Alfaro; Tim Young (Reviews in Aquaculture, 2018)
Aquaculture production is currently challenged to meet the growing demands for seafood protein throughout the world. To achieve this growth in an efficient, safe and sustainable manner, novel tools and applications will need to be incorporated at each step of the production line. A variety of ‘omics’ (e.g. transcriptomics, proteomics, metabolomics) applications have already begun to emerge in aquaculture research with extreme success. A promising new ‘omics’ approach is metabolomics, which aims to use metabolite profiles to identify biomarkers indicative of physiological responses of living samples (e.g. whole organism, tissues, cells) to environmental or culture conditions. One of the benefits of this approach is that it uses a broad scan of biological conditions to identify often unexpected problem or risk areas upon which to focus management attention. In this contribution, we have selected relevant research examples to showcase the applications of metabolomics in aquaculture in four major areas: hatchery production, nutrition and diet, disease and immunology, and post‐harvest quality control. The novelty of this approach is highlighted by the fact that we cite the majority of published papers in this field, and they are all recent (within the last decade) contributions.

Perceptions of Threats Facing Cabo de Palos - Islas Hormigas MPA and Potential Solutions - Katie Hogg; María Semitiel-García; Pedro Noguera-Méndez; Tim Gray; Sarah Young (Coastal Management, 2018)

Investigation of early mussel ( Perna canaliculus ) development using histology, SEM imaging, immunochemistry and confocal microscopy - Adam B. Rusk; Andrea C. Alfaro; Tim Young; Ellie Watts; Serean L. Adams (Marine Biology Research, 2017)

Metabolic profiling of mussel larvae: effect of handling and culture conditions - Tim Young; Andrea C. Alfaro; Silas G. Villas-Bôas (Aquaculture International, 2016)

Putative involvement of adrenergic receptors in regulation of mussel ( Perna canaliculus ) larval settlement - Tim Young; Andrea C. Alfaro; Clara Sánchez-Lazo; John Robertson (Marine Biology Research, 2015)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Development of tri- and tetra- nucleotide polysomic microsatellite markers for characterization of American ginseng (Panax quinquefolius L.) genetic diversity and population structuring - John A. Young; Michael S. Eackles; Marcus J. Springmann; Tim L. King (Conservation Genetics Resources, 2012)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

International workshop on opportunities for ecosystem approaches to fisheries management in the Pacific Ocean tuna fisheries - Valerie Allain; Simon Nicol; Jeffrey Polovina; Marta Coll; Robert Olson; Shane Griffiths; Jeffrey Dambacher; Jock Young; Jesus Jurado Molina; Simon Hoyle; Tim Lawson (Reviews in Fish Biology and Fisheries, 2012)

A Multi-Year Record of Methane Flux at the Mer Bleue Bog, Southern Canada - Tim R. Moore; Allison De Young; Jill L. Bubier; Elyn R. Humphreys; Peter M. Lafleur; Nigel T. Roulet (Ecosystems, 2011)

Integrating Environmental and Socio-Economic Indicators of a Linked Catchment–Coastal System Using Variable Environmental Intensity - John R. Dymond; Tim J. A. Davie; Andrew D. Fenemor; Jagath C. Ekanayake; Ben R. Knight; Anthony O. Cole; Oscar Montes de Oca Munguia; Will J. Allen; Roger G. Young; Les R. Basher; Marc Dresser; Chris J. Batstone (Environmental Management, 2010)

Proteinases involved in matrix turnover during cartilage and bone breakdown - Tim E. Cawston; David A. Young (Cell and Tissue Research, 2010)

Factors affecting the reproductive success of dominant male meerkats - GÖRAN F. SPONG; SARAH J. HODGE; ANDREW J. YOUNG; TIM H. CLUTTON‐BROCK (Molecular Ecology, 2008)
Identifying traits that affect the reproductive success of individuals is fundamental for our understanding of evolutionary processes. In cooperative breeders, a dominant male typically restricts mating access to the dominant female for extended periods, resulting in pronounced variation in reproductive success among males. This may result in strong selection for traits that increase the likelihood of dominance acquisition, dominance retention and reproductive rates while dominant. However, despite considerable research on reproductive skew, few studies have explored the factors that influence these three processes among males in cooperative species. Here we use genetic, behavioural and demographic data to investigate the factors affecting reproductive success in dominant male meerkats ( Suricata suricatta ). Our data show that dominant males sire the majority of all offspring surviving to 1 year. A male's likelihood of becoming dominant is strongly influenced by age, but not by weight. Tenure length and reproductive rate, both important components of dominant male reproductive success, are largely affected by group size and composition, rather than individual traits. Dominant males in large groups have longer tenures, but after this effect is controlled, male tenure length also correlates negatively to the number of adult females in the group. Male reproductive rate also declines as the number of intra‐ and extra‐group competitors increases. As the time spent in the dominant position and reproductive rate while dominant explain > 80% of the total variance in reproductive success, group composition thus has major implications for male reproductive success.

Relationship between assemblages of mycorrhizal fungi and bacteria on grass roots - Brajesh K. Singh; Naoise Nunan; Karyn P. Ridgway; Jim McNicol; J. Peter W. Young; Tim J. Daniell; James I. Prosser; Peter Millard (Environmental Microbiology, 2008)
Summary Soils support an enormous microbial diversity, but the ecological drivers of this diversity are poorly understood. Interactions between the roots of individual grass species and the arbuscular mycorrhizal (AM) fungi and bacteria in their rhizoplane were studied in a grazed, unimproved upland pasture. Individual root fragments were isolated from soil cores, DNA extracted and used to identify plant species and assess rhizoplane bacterial and AM fungal assemblages, by amplifying part of the small‐subunit ribosomal RNA gene, followed by terminal restriction fragment length polymorphism analysis. For the first time we showed that AM fungal and bacterial assemblages are related in situ and that this relationship occurred at the community level. Principal coordinate analyses of the data show that the AM fungi were a major factor determining the bacterial assemblage on grass roots. We also report a strong influence of the composition of the plant community on AM fungal assemblage. The bacterial assemblage was also influenced by soil pH and was spatially structured, whereas AM fungi were influenced neither by the bacteria nor by soil pH. Our study shows that linkages between plant roots and their microbial communities exist in a complex web of interactions that act at individual and at community levels, with AM fungi influencing the bacterial assemblage, but not the other way round.

Comprehensive genetic analyses reveal evolutionary distinction of a mouse ( Zapus hudsonius preblei ) proposed for delisting from the US Endangered Species Act - TIM L. KING; JOHN F. SWITZER; CHERYL L. MORRISON; MICHAEL S. EACKLES; COLLEEN C. YOUNG; BARBARA A. LUBINSKI; PAUL CRYAN (Molecular Ecology, 2006)
Zapus hudsonius preblei , listed as threatened under the US Endangered Species Act (ESA), is one of 12 recognized subspecies of meadow jumping mice found in North America. Recent morphometric and phylogenetic comparisons among Z. h. preblei and neighbouring conspecifics questioned the taxonomic status of selected subspecies, resulting in a proposal to delist the Z. h. preblei from the ESA. We present additional analyses of the phylogeographic structure within Z. hudsonius that calls into question previously published data (and conclusions) and confirms the original taxonomic designations. A survey of 21 microsatellite DNA loci and 1380 base pairs from two mitochondrial DNA (mtDNA) regions (control region and cytochrome b ) revealed that each Z. hudsonius subspecies is genetically distinct. These data do not support the null hypothesis of a homogeneous gene pool among the five subspecies found within the southwestern portion of the species’ range. The magnitude of the observed differentiation was considerable and supported by significant findings for nearly every statistical comparison made, regardless of the genome or the taxa under consideration. Structuring of nuclear multilocus genotypes and subspecies‐specific mtDNA haplotypes corresponded directly with the disjunct distributions of the subspecies investigated. Given the level of correspondence between the observed genetic population structure and previously proposed taxonomic classification of subspecies (based on the geographic separation and surveys of morphological variation), we conclude that the nominal subspecies surveyed in this study do not warrant synonymy, as has been proposed for Z. h. preblei , Z. h. campestris , and Z. h. intermedius .

Improvement of Dissolution Rates of Poorly Water Soluble APIs Using Novel Spray Freezing into Liquid Technology - Jiahui Hu; True L. Rogers; Judith Brown; Tim Young; Keith P. Johnston; Robert O. Williams III (Pharmaceutical Research, 2002)